Інституційна структура та ефективність функціонування Світової організації торгівлі - Скринька, Д. В.; Скрынька, Д. В.; Skryn'ka, D. (My University, 2012)
The article deals with the analysis of the infl uence of the WTO institutional structure upon the effectiveness of this international organization. The article, reviews, inter alia, the functional connection between the WTO bodies and the WTO international agreements. The article points out that the WTO style of dispute settlement is especially important factor of the overall effi ciency of this international organization.
Скринька Д. В. Інституційна структура та ефективність функціонування Світової організації торгівлі / Д. В. Скринька // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 46. – С. 82-89.
Keywords: інституційна структура Світової організації торгівлі; зв’язок між органами СОТ та міжнародними договорами; система врегулювання спорів в СОТ; институционная структура Всемирной торговой организации; связь между органами ВТО и международными договорами; система урегулирования споров в ВТО; institutional structure of the World Trade Organization; relationship between the WTO and international agreements; dispute settlement system of the WTO